Luxembourg : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This 2012 Article IV Consultation highlights that economic growth in Luxembourg slowed in 2011 amid the euro area sovereign debt crisis. Reflecting sluggish external demand, economic activity is expected to further weaken, with growth projected to decline to 1\2 percent in 2012. Executive Directors have welcomed the continued stability of Luxembourg's economy despite the turbulence in the euro area. They have commended the authorities on measures taken to strengthen the financial sector and to implement recommendations from the Financial Stability Assessment Program update.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet